The effect of type of task on EFL learners’ vocabulary learning - Eskandari, Zahra; Khatin-Zadeh, Omid; Farsani, Danyal; Banaruee, Hassan (Frontiers in Psychology, 2024)
Depth of processing vocabulary has been the subject of heated discussion among vocabulary researchers. Yet, current literature lacks research comparing different tasks to investigate the acquisition of vocabulary knowledge among adult learners of English as a foreign language (EFL). To fill the gap, we designed five task-based groups based on Technique Feature Analysis (TFA) as a framework to predict the effectiveness of different vocabulary learning tasks with similar or different TFA rankings on L2 vocabulary knowledge gain. The participants were 130 EFL learners (mean age = 21.7, female 61.5%) randomly assigned to the vocabulary learning tasks: reading and multiple-choice items (TFA=6), reading and choosing definitions (TFA=6), reading and fill-in-the-blanks (TFA=7), reading and rewording the sentences (TFA=6) and composition writing (TFA=8). The results of the study revealed that tasks with the same TFA scores led to similar vocabulary knowledge gains. While predictions of the TFA are partially supported, composition writing and sentence rewording tasks supersede other tasks in terms of their effectiveness in vocabulary acquisition.